Comparison and evaluation for the dose distribution and physical characteristics between two AAA and AXB algorithms in Eclipse v13.6 software on treatment plans in regions heterogenous densities at 108 Military Central Hospital - Thai, Hoang Huu; Dat, Nguyen Tien; Anh, Nguyen Thi Van; Lam, Pham Hong; Linh, Bui Duy; Duc, Le Manh; Trung, Pham Quang (Nuclear Science and Technology, 2020)
The aim of this study is to compare and evaluate the dose distribution and physical characteristics of two algorithms Anisotropic Analytical Algorithm (AAA) and Acuros XB (AXB) inEclipse v13.6 software in regions heterogeneous densities. Computed Tomography Simulation (CT –Sim) data of 48 treated cancer patients (20 head and neck cancer (H&N) patients, 15 esophageal cancer patients, 8 lung cancer patients with 3 Dimensions Conformal Radiation Therapy (3D-CRT)and 5 lung cancer patients treated with Volumetric Modulated Arc Therapy (VMAT)) were used to replan the Eclipse v13.6 software with two algorithm AAA and AXB. For all plans, the Quality of Coverage (Q), the Conformity Index (CI), the Homogeneity Index (HI) and the dose volume histograms (DVH) for the targets and the organs at risk (OARs) were compared and evaluated. Pretreatment quality assurance (QA) was performed using the Electronic Portal Imaging Device(EPID) for all VMAT plans, and the gamma index method was used to qualify the agreement between calculations and measurements. In addition, total Monitor Units (MUs) and the calculation time were investigated. The indicators obtained from the H&N VMAT plans calculated by AAA close to ideal values than AXB. The total MUs obtained from two algorithms are approximately equal. The lung cancer 3D – CRT plans, the indicators for target and OARs are approximately the same. However, the calculation time of the AAA is faster than the AXB from 7.5 to 14 times. The indicator obtained from the lung cancer VMAT plans calculated by two algorithms AAA and AXB are approximately equal. The total MUs and time calculation are approximate the same. However, the V5, V10, V20 and Mean Lung Dose (MLD) obtained from AAA is lower than AXB. For esophageal cancer VMAT plans, the indicators HIRTOG, HIWu, and Q calculated by AAA close to the ideal values than AXB. However, the indicators CIPaddick, CIICRU-62, V5, V10, V20 and MLD calculated by AXB are better than AAA. The dose distribution indicators obtained from AAA algorithm are better than AXB algorithm in H&N cancer and lung cancer plans. For the esophageal cancer plans, AXB algorithm gave the dose distribution indicator are better than AAA.